Spectroscopic studies of self-assembled plasmonic nanoparticle arrays - Verre, Ruggero (Trinity College (Dublin, Ireland). School of Physics, 2011)
In this thesis an alternative self-assembled deposition technique able to produce nanoparticle (NP) arrays ordered on the macroscale is described. Stepped surfaces are produced by high temperatures annealing AI3O4 (0001) and metals are evaporated at a glancing angle of incidence towards the surface. In this way NPs are produced on a transparent and insulating substrate. These structures show localised plasmon resonances whose energetic positions depend on the polarization of the exciting light, the template deposition, the NP size as well as the distance between the NPs.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.